Molecular subtyping of CD5+ diffuse large B-cell lymphoma based on DNA-targeted sequencing and Lymph2Cx - Ma, Dongshen; Ma, Yuhan; Ma, Yuanyuan; Liu, Jia; Gu, Ying; Liu, Nian; Xiang, Chenxi; Liu, Hui; Sang, Wei (Frontiers in Oncology, 2022)
Background: CD5-positive diffuse large B-cell lymphoma (CD5+ DLBCL) showed a poor prognosis in the rituximab era, with limited research on its genetic characteristics and cell-of-origin (COO). We aimed to demonstrate the molecular characteristics of CD5+ DLBCL, and to discover potential prognostic factors. Methods: We included 24 cases of CD5+ DLBCL and 23 CD5- counterparts and collected their clinicopathological features. Targeted DNA sequencing of 475 lymphoma-related genes was performed and all cases were assigned to distinct genetic subtypes using the LymphGen tool. The COO was determined by the Lymph2Cx assay. The Kaplan–Meier method and Cox proportional hazard model were applied to identify the possible prognostic factors. Results: Compared with their CD5- counterparts, patients with CD5+ DLBCL tended to have a worse prognosis and a higher incidence of MCD (MYD88 L265P and CD79B double mutations) subtype (54.17%, P = 0.005) and activated B-cell like (ABC) subtype (62.5%, P = 00017), as determined by next-generation sequencing and Lymph2Cx, respectively. Moreover, PIM1, MYD88, and KMT2D mutations were detected more frequently in CD5+ DLBCL cases (P < 0.05). According to multivariate analysis, MYC/BCL2 double expression and ABC subtype were correlated with unfavorable overall survival (OS). High mRNA expression of SERPINA9 and MME showed a significant correlation with a better OS, and high expression of MME showed a significant correlation with better progression-free survival in CD5+ DLBCL. Conclusion: The genetic profile of CD5+ DLBCL is characterized by PIM1, MYD88 and KMT2D mutations, with a higher incidence of MCD and ABC subtypes. MYC/BCL2 double expression, ABC subtype and mRNA expression of SERPINA9 and MME are independently predictive of the prognosis of CD5+ DLBCL.